Association Between Family History and Hypertension Among Chinese Elderly. Issue 48 (December 2015) - Liu, Miao; He, Yao; Jiang, Bin; Wang, Jianhua; Wu, Lei; Wang, Yiyan; Zhang, Di; Zeng, Jing; Yao, Yao
Abstract : Abstract: This study aimed to evaluate the association between family history and prevalence of hypertension among Chinese community elderly, and also explore the gender difference. A population-based cross-sectional study was conducted in Miyun district of Beijing, in 2014. The family history information was obtained from each subject and was divided into 3 categories, no family history (FH0), 1 generation of first-degree relatives with hypertension (FH1), and 2 generations of first-degree relatives with hypertension (FH2). The prevalence of hypertension was 53.0%. Participants with positive family history had a significantly higher prevalence of hypertension (67.5%, 95% CI: 63.3–71.7) than those without (47.9%, 95% CI: 45.2–50.6), and even among participants without hypertension, the blood pressure levels were higher with positive FH. Multiple logistic regression analysis showed that a significantly linear-trend increase in hypertension according to family history of first degree relative numbers was observed in both genders ( P for trend < 0.001). This study suggests that family history had not only a significant but also graded association with hypertension and with blood pressure levels, and this association exists even among those without hypertension. Abstract : Supplemental Digital Content is available in the text